A Study of Speaking Anxiety of English Study Program Students FKIP UNRI (West Science Social and Humanities Studies, 2026)
Speaking anxiety is one of the common problems experienced in the classroom learning process. This study aims to identify the level of students’ speaking anxiety and the factors causing speaking anxiety. This study was quantitative research with a descriptive quantitative design. Quantitative data were obtained through a questionnaire adapted from the Foreign Language Classroom Anxiety Scale (FLCAS), followed with qualitative data were collected through interviews. The population of this study consisted of fifth-semester students of the English Study Program, Faculty of Teacher Training and Education, Universitas Riau. The researcher used cluster sampling as the sampling technique, with three classes (5A, 5B, and 5C) as the sample, consisting of 115 students. The results of the study show that most students were at a relatively high level of anxiety, categorized as Anxious level. The findings indicate that anxiety was influenced by several factors, with fear of negative evaluation as the most dominant, followed by lack of understanding of the topic being discussed, lack of preparation, lack of confidence, and afraid of making mistakes. This study concludes that speaking anxiety is an experience felt by students that not only influenced by linguistic aspects but also by psychological factors and the learning environment.